2005
DOI: 10.1152/ajpheart.00767.2004
|View full text |Cite
|
Sign up to set email alerts
|

Influences of breathing patterns on respiratory sinus arrhythmia in humans during exercise

Abstract: Blain, Grégory, Olivier Meste, and Stéphane Bermon. Influences of breathing patterns on respiratory sinus arrhythmia in humans during exercise. Am J Physiol Heart Circ Physiol 288: H887-H895, 2005. First published September 23, 2004 doi:10.1152/ajpheart. 00767.2004.-Persistence of respiratory sinus arrhythmia (RSA) has been described in humans during intense exercise and attributed to an increase in ventilation. However, the direct influence of ventilation on RSA has never been assessed. The dynamic evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 40 publications
7
85
1
1
Order By: Relevance
“…It is interesting, however, that the greater variability of V T did not translate into greater variability in arterial pressure [19]. The amplitude of RSA, as indicated by the HF component of HRV, was proportionally increased or reduced by increases or decreases in V T , respectively, when B f was kept constant [29], thus suggesting a direct influence of lung inhalation on HF amplitude. Others [30] have reported that phasic inputs from pulmonary and thoracic stretch receptors make only a small contribution to R-R variability at respiratory frequency, though it has been suggested that changes in both B f and V T be taken into account when using HRV to explore cardiac autonomic regulation [31].…”
Section: Discussionmentioning
confidence: 92%
“…It is interesting, however, that the greater variability of V T did not translate into greater variability in arterial pressure [19]. The amplitude of RSA, as indicated by the HF component of HRV, was proportionally increased or reduced by increases or decreases in V T , respectively, when B f was kept constant [29], thus suggesting a direct influence of lung inhalation on HF amplitude. Others [30] have reported that phasic inputs from pulmonary and thoracic stretch receptors make only a small contribution to R-R variability at respiratory frequency, though it has been suggested that changes in both B f and V T be taken into account when using HRV to explore cardiac autonomic regulation [31].…”
Section: Discussionmentioning
confidence: 92%
“…Contrary to previous studies (Cottin et al 2004;Tulppo et al 1999), the current study examined steady-state submaximal exercise of various modes with greater HRV maintained during UB exercise compared to WB and LB exercise, despite the same HR (Tables 2, 3). The greater HRV during UB may reflect greater respiratory-induced sinus arrhythmia as changes in respiration, particularly respiratory rate, have been reported to alter HRV (Blain et al 2005;Brown et al 1993). However, this was unlikely in the current study given that Resp was significantly lower for LB compared to WB with similar HRV, while Resp was similar between WB and UB with significantly greater HRV for UB compared to WB.…”
Section: Heart Rate Variability and Exercisementioning
confidence: 99%
“…The Wingate test was aimed at markedly increasing sympathetic and reducing vagal activities (Goulopoulou et al 2006) prior to the start of the submaximal exercise bout, so that the confounding effect of sympathetic overactivity (i.e., interaction; Levy 1971) on the post-exercise parasympathetic reactivation response to both recovery conditions could be investigated. As well, analyzing autonomic responses to submaximal, but not maximal exercise, was designed to observe the influence of the presumed sympathetic overactivity on post-exercise HRV indices, whilst eliminating the potential confounding mechanical effects of high minute ventilation on the HF power density (Blain et al 2005). …”
Section: Wingate Testmentioning
confidence: 99%